Interactive effect of corn particle size and insoluble fiber source on performance, nutrient utilization and intestine morphology in broilers fed pelleted diets. Issue 6 (12th April 2021) - Moradi, Soudabeh; Moradi, Arash; Atabaigi Elmi, Vahid; Reza Abdollahi, Mohammad
Abstract: The effects of corn particle size and dietary fibre on the performance, coefficient of apparent ileal digestibility (CAID) and intestinal characteristics in broiler starters fed pelleted diets were studied. The experiment included 10 treatments arranged as a 2 × 5 factorial with two corn particle sizes (GMD of 1071 [CGC] vs. 534 [FGC]) and five diets that consisted in a low‐fibre diet and four extra diets resulting from the inclusion of insoluble fibre sources (10 g/kg of lignocellulose (LC), and 30 g/kg of oat hulls; OH, rice hulls; RH, and sunflower hulls; SFH). In coarse grinding, all‐fibre sources improved body weight gain and feed intake compared to the control diet ( p < 0.01). Feed conversion ratio (FCR) improved with fibre supplementation ( p < 0.01) and fine grinding of corn (FGC) ( p < 0.01). Coarse grinding of corn (CGC) and inclusion of RH, SFH and OH reduced gizzard pH ( p < 0.01). Fibre inclusion increased ileal fat and Ca digestibility ( p < 0.01), gizzard weight ( p < 0.01), digesta transit time ( p < 0.01) and length of duodenum and small intestine ( p < 0.01). The CAID of phosphorus increased in CGC fed birds and inclusion of RH, SFH and OH ( p < 0.05). The weight of gizzard, proventriculus and pancreas ( p < 0.01) was greater in CGC fed birds. Feeding SFH, RH and OH ( p < 0.01), and CGC ( p < 0.01) increased the villus height (VH) of the duodenum. The OH, RH and SFH supplementation increased the caecal population of Lactobacillus spp. and total anaerobic bacteria ( p < 0.01) only in FGC fed birds. Overall, birds fed pelleted diets containing RH, OH and SFH (3%) exhibited improved performance, and increased nutrient digestibility, which may be caused by developed gizzards and intestine. Furthermore, coarse grinding of corn is beneficial to gizzard development.